Melatonin and Cardioprotection in Humans: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Domínguez-Rodríguez, Alberto; Abreu-González, Pedro; Báez-Ferrer, Néstor; Reiter, Russel J.; Avanzas, Pablo; Hernández-Vaquero, Daniel (Frontiers in Cardiovascular Medicine, 2021)
Myocardial ischemia/reperfusion (IR) injury represents a critical problem associated with interventional approaches for coronary reperfusion. Pharmacological cardioprotective interventions are advocated to ameliorate IR injury. Melatonin is an anti-inflammatory and antioxidant agent with a wide range of therapeutic properties that may contribute to its cardioprotective effects. No systematic review or meta-analysis has compared melatonin versus placebo as a cardioprotective agent in humans. The present study, based on a systematic review and meta-analysis, was carried out to assess melatonin’s efficacy as a cardioprotective treatment. We performed a systematic review of the available literature. Randomized controlled trials (RCTs) were identified and information was extracted using predefined data extraction forms. The primary outcomes were (a) left ventricular ejection fraction (LVEF) and (b) blood troponin levels in patients who underwent myocardial revascularization and were randomized to melatonin or placebo. The inverse-variance random-effects method was used to pool the estimates. Heterogeneity and publication bias were assessed. Weighted mean differences or standardized mean differences were calculated. A total of 283 records were screened and seven RCTs met all the inclusion criteria. After the pooled analysis, the results on LVEF were consistent across all studies, a significant heterogeneity was found in results on troponin levels. The melatonin-treated patients had on average higher LVEF than the placebo-treated individuals with a weighted mean difference =3.1% (95%CI 0.6%-5.5%, p=0.01). Five works compared levels of troponin after melatonin or placebo treatment. The melatonin-treated patients had lower levels of troponin with a standardized mean difference= -1.76 (95%CI -2.85 - -0.67, p=0.002). The findings of this meta-analysis revealed that melatonin administration in humans as cardioprotective agent attenuated heart dysfunction with a favourable effect on the LVEF.